2013
DOI: 10.1159/000347123
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the ‘Repositioning Test' on Postoperative Outcome of Retroluminar Transobturator Male Sling Implantation

Abstract: Objective: To evaluate prospectively the value of the ‘repositioning test' (RT) in preoperative patient selection for the efficacy of male stress urinary incontinence (SUI) treatment using a retroluminar transobturator male sling (AdVance sling). Patients and Methods: 65 consecutive patients with SUI after radical prostatectomy were included in this single-center prospective study. Preoperatively, patients were classified into those with ‘positive' and ‘negative' RT. Postoperative results were analyzed and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 11 publications
5
47
1
3
Order By: Relevance
“…After a mean follow-up of 17.3 months, they observed significantly worse efficacy outcomes for previously irradiated patients; however, the authors do not state if an exhaustive cystoscopic evaluation, including a repositioning test to determine the coaptive urethral zone, was performed. A short coaptive zone, however, has been shown to be an important predictive factor of treatment failure after AdVance implantation [7,21]. Consistent with these results, the present findings highlight the impact of preoperative clinical assessment and subsequent patient selection and indicate that good long-term results can be achieved in carefully selected patients even if the medical history includes suboptimal features.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…After a mean follow-up of 17.3 months, they observed significantly worse efficacy outcomes for previously irradiated patients; however, the authors do not state if an exhaustive cystoscopic evaluation, including a repositioning test to determine the coaptive urethral zone, was performed. A short coaptive zone, however, has been shown to be an important predictive factor of treatment failure after AdVance implantation [7,21]. Consistent with these results, the present findings highlight the impact of preoperative clinical assessment and subsequent patient selection and indicate that good long-term results can be achieved in carefully selected patients even if the medical history includes suboptimal features.…”
Section: Discussionsupporting
confidence: 87%
“…A daily pad usage of 1-3 pads was further defined as mild incontinence. In addition, a mandatory urethroscopic evaluation of the sphincter, including a repositioning test and assessment of the coaptive urethral zone, was performed as previously described [7]. To detect potential cutting down of drinking that could mask more severe stress urinary incontinence, fluid drinking habits were assessed preoperatively and patients were advised to reach a daily fluid intake of at least 1.5 L daily.…”
Section: Patient Population Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…One could argue that the inclusion of such patients may lead to overestimation of the overall risk of complications. However, when we stratified patients on the bases of exposure to radiations, we observed an erosion rate of 26.8% among radiation-naïve patients, which is consistent with what has been reported by Lima et al [11] and significantly higher compared to the reports by Schiavini et al [9] and Introini et al [16]. …”
Section: Discussionsupporting
confidence: 91%
“…Second, our study provides long-term follow-up data, which is mandatory for the accurate understanding of risks and benefits related to a relatively novel technology such as the Silimed PC. This was confirmed by Lima et al [11] who recently analyzed a retrospective series of 56 patients. The authors reported that 41% of patients required removal of the device after a mean follow-up of 82.2 months.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation